2019
DOI: 10.24036/jce.v2i4.135
|View full text |Cite
|
Sign up to set email alerts
|

Youtube Sebagai Sumber Belajar Generasi Milenial

Abstract: Penelitian ini bertujuan untuk mengetahui bagaimana pemanfaatan media YouTube sebagai salah satu sumber belajar mahasiswa pada matakuliah rumpun politik kewarganegaraan ditinjau dari aspek penggunaan, tindak lanjut yang dilakukan, manfaat yang diperoleh, serta kendala apa saja yang dialami oleh mahasiswa Jurusan Ilmu Sosial Politik dalam menggunakan media YouTube sebagai sumber belajar. Lokasi penelitian ini berada di lingkungan Fakultas Ilmu Sosial Universitas Negeri Padang dan lingkungan sekitar tempa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
22

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(53 citation statements)
references
References 0 publications
1
11
0
22
Order By: Relevance
“…Moreover, the use of youtube application that is being widely utilized for all circles from children to adults as a means of entertainment and a means of finding information, for that youtube application can be referred to as a source of learning millennials (Setiadi et al, 2019…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the use of youtube application that is being widely utilized for all circles from children to adults as a means of entertainment and a means of finding information, for that youtube application can be referred to as a source of learning millennials (Setiadi et al, 2019…”
Section: Discussionmentioning
confidence: 99%
“…Finally, research by Jackman (2019) revealed the success of Youtube as an e-resource in facilitating and guiding students in learning. Some challenges related to the use of YouTube in learning expressed by Suryaman (in Setiadi, Azmi, & Indrawadi, 2019) are found, namely: 1) Video availability, on the YouTube, several videos are only available within a specific time, so students or educators must consider the availability of the videos (Burke & Snyder, 2008). 2) Quality of Content, for videos, to not be outdated, YouTube users, especially students and educators, must pay attention to the date of the video.…”
Section: The Use Of Youtube As a Learning Resourcementioning
confidence: 99%
“…3) The search process, the next challenge is in the video search process. A video search can produce abundant video displays that confuse users in choosing a video to get appropriate information (Setiadi et al, 2019). Thus, the considerations in making Youtube content as a learning resource are (1) shortening the video duration with a brief, concise, and clear explanation because the shorter video will not be boring for students in the implementation of the learning process, (2) signaling or the emphasis in every material on Youtube because students prefer the clarity or conclusions of a material provided and (3) management of learning videos centered in one Youtube channel.…”
Section: The Use Of Youtube As a Learning Resourcementioning
confidence: 99%
“…Teknologi Informasi adalah suatu teknologi yang digunakan untuk mengolah data. Pengolahan itu termasuk menyimpan, menyusun, mendapatkan, memproses, memanipulasi data dalam berbagai cara untuk menghasilkan informasi yang berkualitas, yaitu informasi yang akurat, tepat waktu, dan relevan [6].…”
Section: Pendahuluan a Latar Belakangunclassified